Evenhandedness of Fund Surveillance : Principles and Mechanism for Addressing Concerns. (Policy Papers; Policy Paper, 2016)
Evenhandedness of the Fund's analysis and advice is critical to the effectiveness of its engagement with member countries. In this regard, both actual and perceived lack of evenhandedness can be detrimental to the Fund's credibility and legitimacy. While perceptions of evenhandedness often reflect views about the full range of Fund activities, Fund surveillance is an important contributor to perceptions. Moreover, the consistency of the Fund's analysis and advice will likely be scrutinized more closely in an interconnected world.